How to Sharpen Words: Mayakovsky's Machines of Poetic Humour. (May 2014) - McGavran, James
Abstract : Analysis of Mayakovsky's prose writings of the mid-1920s on the craft of satire reveals that he understood it to be a scientific discipline subject to strict cause-and-effect relationships: if the satirical treatment of a theme — any theme — is correct, then the piece will produce 'involuntary laughter' ( neproizvol'nyi smekh ). As an example, he puts forward his 1923 poem 'Schematic of Laughter' ( Skhema smekha ) — a text he claims contains no comic ideas, but only the correct satirical sharpening of discourse. As a barebones inventory of comic devices, the poem is a perfect place to begin an examination of Mayakovsky's poetics of humour. But it is not alone; in a note to the 1925 poem 'Shallow Philosophy in Deep Places' ( Melkaia filosofiia na glubokikh mestakh ), Mayakovsky explains that it too is a 'skeleton poem' ( stikh-skelet ), just like the 'Schematic', and another compendium of humorous devices. Together, then, these poems represent the purest and most concentrated expression of Mayakovsky's understanding of the mechanics of poetic humour. Sustained close reading of both poems reveals that his humorous devices, ranging from formal to narrative, all serve to establish and then deceive expectations in the reader.